2004
DOI: 10.1902/jop.2004.75.6.893
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in Location of the Mucogingival Junction 5 Years After Coronally Repositioned Flap Surgery

Abstract: Within the limits of this study, the 60-month follow-up findings indicated that the CRF procedure failed to maintain the gingival tissue in a coronal position and that the observed movement of the MGJ back to its original position was partially dependent on the apical movement of gingival margin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
34
1
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(44 citation statements)
references
References 25 publications
5
34
1
1
Order By: Relevance
“…Last, KT height increase in the Cort group may have been attributable to apical movement of the MGJ, but apical migration is highly unlikely. [44][45][46] In the present study, it would appear that the most cogent explanation for mandibular anterior labial KT height increase in the Cort group was stretching the full-thickness flap coronally over the buccolingual bulk of augmentation grafting material. Although the main purpose of alveolar corticotomy and bone grafting is not to increase KT height, it would appear that the procedure results in this value-added outcome.…”
Section: Discussionmentioning
confidence: 91%
“…Last, KT height increase in the Cort group may have been attributable to apical movement of the MGJ, but apical migration is highly unlikely. [44][45][46] In the present study, it would appear that the most cogent explanation for mandibular anterior labial KT height increase in the Cort group was stretching the full-thickness flap coronally over the buccolingual bulk of augmentation grafting material. Although the main purpose of alveolar corticotomy and bone grafting is not to increase KT height, it would appear that the procedure results in this value-added outcome.…”
Section: Discussionmentioning
confidence: 91%
“…Lower degrees of RC were reported by other authors in long‐term studies. Gürgan et al (2004) reported a mean RC of 68.3% after 12 months and 44.9% after 60 months following the CAF procedure. Superior results than the ones obtained in the present study were also reported as mean 98.6% and 96.7% RC after 12 and 36 months after surgery, respectively (deSanctis & Zucchelli 2007).…”
Section: Discussionmentioning
confidence: 97%
“…It is recognized that the CPF may provide excellent root coverage (>97%) in the treatment of Miller Class I recessions (4 mm) (Allen & Miller 1989, Harris & Harris 1994, Wennström & Zucchelli 1996). However, it has also been shown that after this procedure the coronal position of the gingival margin may not be stable, showing 68.2% of mean percentage root coverage at the end of 1 month and 44.8% after 60 months (Gurgan et al 2004). Considering the studies using ADM, 99% of root coverage was obtained after 6 months (Woodyard et al 2004).…”
Section: Discussionmentioning
confidence: 99%